SHOOT GROWTH RESPONSES AT SUPPLEMENTARY FEEDING STATIONS FOR MOOSE IN NORWAY - Mathisen, Karen Marie; Rémy, Amandine; Skarpe, Christina (Lakehead University, 2015)
Moose browsing pressure in the vicinity of supplementary winter feeding stations eventually declines over time. It is believed that continual winter browsing over multiple years causes locally reduced shoot growth and forage availability for moose (Alces alces). We tested this hypothesis by comparing the size of annual shoots of Scots pine (Pinus sylvestris), downy birch (Betula pubescens), and Norway spruce (Picea abies) along a distance gradient from supplementary feeding stations. Contrary to our hypothesis, we found that shoot size was larger at feeding stations than at distances out to 1500 m. This increase in shoot size was probably not related directly to browsing, but to higher nutrient and light availability associated with moose activity at feeding stations. Increased use of Norway spruce, yet reduced browsing overall at feeding stations, probably reflects the overall decline in abundance of preferred Scots pine and downy birch in a local environment substantially altered by an artificially and abnormally high density of moose.